An Investigation into the use of Social Media by Small Businesses - Hallam, Thomas Alexander (2015)
This research sought to contribute to our understanding of the specific everyday challenges which small and medium sized enterprises face when attempting to engage with consumers on social media. In pursuit of this, research questions focused on identifying the barriers which SME’s face when implementing social media strategies and the organisational capabilities required to improve strategy respectively. A lack of “effective measurement techniques”, being naturally “social media-ready”, the “scarcity of time" and the “challenge of content creation” were the most significant barriers highlighted by the respondents in this research. In terms of capabilities, “Speed and Flexibility”, “Content Generation” and the “Measurement of Social Media impact” are found by this research to be the most crucial to the development of an organisations social media strategy.